2015
DOI: 10.1111/jac.12128
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Delayed Flowering and Reduced Reproductive Success of Chickpea (Cicer arietinum L.), A Response Associated with Na+ Accumulation in Leaves

Abstract: Salinity is known to reduce chickpea yields in several regions of the world. Although ion toxicity associated with salinity leads to yield reductions in a number of other crops, its role in reducing yields in chickpea growing in saline soils is unclear. The purpose of this study was to (i) identify the phenological and yield parameters associated with salt stress tolerance and sensitivity in chickpea and (ii) identify any pattern of tissue ion accumulation that could relate to salt tolerance of chickpea expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
(67 reference statements)
1
31
1
Order By: Relevance
“…In order to survive under salt stress conditions, plants tend to accelerate the vegetative phase and enter into reproductive phase i.e. flowering and podding (Pushpavalli et al 2015). In contrast, in the present study, a delayed in flowering, hence in pod formation was observed under salt stress in both the genotypes.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In order to survive under salt stress conditions, plants tend to accelerate the vegetative phase and enter into reproductive phase i.e. flowering and podding (Pushpavalli et al 2015). In contrast, in the present study, a delayed in flowering, hence in pod formation was observed under salt stress in both the genotypes.…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast, in the present study, a delayed in flowering, hence in pod formation was observed under salt stress in both the genotypes. Reduction in pod number could be associated with the salt-induced negative effects on nutrient contents and/or on sucrose metabolism which might have reduced the activities of apoplastic and cytoplasmic sucrose cleaving enzymes (Pushpavalli et al 2015). They further correlated decline in seed yield with filled pod and seed number but not with seed size.…”
Section: Discussionmentioning
confidence: 97%
“…; Ramesh et al , Borrás et al , Betzelberger et al ). Some examples of such association between physiological and ionic traits are seen with grain yield in wheat (Zhu et al ) and also in chickpea under salinity (Pushpavalli et al ). Nevertheless, this is the first study demonstrating the potential of gaseous exchange (P net , E, gs), oxidative damages, (H 2 O 2 , O 2 •‐ , MDA), antioxidants (AsA, PPO, PAL, GPX) and ionic (Na + , Cl − , K + , Mg 2+ , Ca 2+ , SO 4 2− ) variables of root and leaves to elucidate the quinoa yield variations when grown under high salt‐stressed conditions with or without soil drenching of PBZ.…”
Section: Discussionmentioning
confidence: 99%
“…As has been documented extensively, it is essential for plants to maintain low concentrations of toxic ions in leaves to grow and survive under salt stress. It has been found that many plants, e.g., Populus euphratica 50, Cicer arietinum L51 and Jatropha curcas 52, can effectively prevent Na + and Cl − uptake under salt stress. In our study, under saline conditions, the Na + concentrations in the shoots of male plants were significantly lower than those in the roots, indicating the efficient inhibition of root-shoot Na + transport in males.…”
Section: Discussionmentioning
confidence: 99%